(untitled) (International Seven Journal of Multidisciplinary, 2022)
This article examines the relationship between diet and longevity, highlighting the impact of specific eating patterns and nutrient intake on life expectancy and healthy aging. It discusses the role of balanced diets, rich in whole foods, fruits, vegetables, legumes, whole grains, and healthy fats, in reducing the risk of chronic diseases such as cardiovascular disease, type 2 diabetes, and certain cancers. The review also addresses the influence of cultural, socioeconomic, and lifestyle factors on dietary habits and health outcomes. Furthermore, it presents evidence from epidemiological studies and meta-analyses that link Mediterranean, plant-based, and calorie-restricted diets to increased lifespan and improved quality of life. The findings suggest that promoting healthy eating habits is a key public health strategy to enhance longevity and reduce the global burden of chronic illnesses.